GWAS on prolonged gestation (post-term birth): analysis of successive Finnish birth cohorts. Issue 1 (10th October 2017) - Schierding, William; Antony, Jisha; Karhunen, Ville; Vääräsmäki, Marja; Franks, Steve; Elliott, Paul; Kajantie, Eero; Sebert, Sylvain; Blakemore, Alex; Horsfield, Julia A; Järvelin, Marjo-Riitta; O'Sullivan, Justin M; et al.
Abstract : Background: Gestation is a crucial timepoint in human development. Deviation from a term gestational age correlates with both acute and long-term adverse health effects for the child. Both being born preterm and post-term, that is, having short and long gestational ages, are heritable and influenced by the prenatal and perinatal environment. Despite the obvious heritable component, specific genetic influences underlying differences in gestational age are poorly understood. Methods: We investigated the genetic architecture of gestational age in 9141 individuals, including 1167 born post-term, across two Northern Finland cohorts born in 1966 or 1986. Results: Here we identify one globally significant intronic genetic variant within the ADAMTS13 gene that is associated with prolonged gestation (p=4.85×10 −8 ). Additional variants that reached suggestive levels of significance were identified within introns at the ARGHAP42 and TKT genes, and in the upstream (5') intergenic regions of the B3GALT5 and SSBP2 genes. The variants near the ADAMTS13, B3GALT5, SSBP2 and TKT loci are linked to alterations in gene expression levels (cis-eQTLs). Luciferase assays confirmed the allele specific enhancer activity for the BGALT5 and TKT loci. Conclusions: Our findings provide the first evidence of a specific genetic influence associated with prolonged gestation. This study forms a foundation for a better understanding of the genetic and long-term health risks faced by induced and post-term individuals. The long-term risks for induced individuals who have a previously overlooked post-term potential may be a major issue for current health providers.